Comparing the effectiveness of using generic and specific search terms in electronic databases to identify health outcomes for a systematic review: a prospective comparative study of literature search methods. Issue 3 (25th June 2012) - Egan, Matt; MacLean, Alice; Sweeting, Helen; Hunt, Kate
Abstract : Objective: To compare the effectiveness of systematic review literature searches that use either generic or specific terms for health outcomes. Design: Prospective comparative study of two electronic literature search strategies. The 'generic' search included general terms for health such as 'adolescent health', 'health status', 'morbidity', etc. The 'specific' search focused on terms for a range of specific illnesses, such as 'headache', 'epilepsy', 'diabetes mellitus', etc. Data sources: The authors searched Medline, Embase, the Cumulative Index to Nursing and Allied Health Literature, PsycINFO and the Education Resources Information Center for studies published in English between 1992 and April 2010. Main outcome measures: Number and proportion of studies included in the systematic review that were identified from each search. Results: The two searches tended to identify different studies. Of 41 studies included in the final review, only three (7%) were identified by both search strategies, 21 (51%) were identified by the generic search only and 17 (41%) were identified by the specific search only. 5 of the 41 studies were also identified through manual searching methods. Studies identified by the two ELS differed in terms of reported health outcomes, while each ELS uniquely identified some of the review's higher quality studies. Conclusions: Electronic literature searches (ELS) are a vital stage in conducting systematic reviews and therefore have an important role in attempts to inform and improve policy and practice with the best available evidence. While the use of both generic and specific health terms is conventional for many reviewers and information scientists, there are also reviews that rely solely on either generic or specific terms. Based on the findings, reliance on only the generic or specific approach could increase the risk of systematic reviews missing important evidence and, consequently, misinforming decision makers. However, future research should test the generalisability of these findings.